THE IMPACT OF TIME AND SPACE CONSTRAINTS ON CHILD AUTONOMY AND SOCIAL DEVELOPMENT IN KINDERGARTEN - WangQian; Rahman, Mohd Nazri Abdul; Affandi, Ghozali Rusyid (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the impact of time and space constraints in kindergarten settings on children’s autonomy, emotional well-being, and social development. Method: A mixed-methods approach was employed, combining classroom observations (N = 60), teacher interviews (N = 20), and structured surveys (N = 50). Quantitative analyses, including ANOVA, correlation analysis, and Structural Equation Modeling (SEM), were conducted to examine the relationships between environmental constraints and developmental outcomes. Results: Findings revealed that 72% of children exhibited signs of frustration due to rigid scheduling, while 74% of teachers identified limited social interaction opportunities as a major concern. Regression analysis indicated that time rigidity significantly predicted increased stress levels in children (β = 0.42, p < 0.05), whereas spatial flexibility was positively associated with peer collaboration (β = 0.52, p < 0.01). Qualitative data supported these results, highlighting teacher concerns about inflexible routines and limited classroom adaptability. Furthermore, children in open-space classrooms engaged in 30% more peer interactions compared to those in traditionally arranged settings. Novelty: This study provides empirical evidence supporting the benefits of flexible time and spatial arrangements in early childhood education. The findings emphasize the importance of child-centered scheduling and dynamic classroom environments in promoting holistic development. Policy recommendations include reducing time rigidity, integrating more child-led activities, and adopting adaptive classroom designs to enhance learning outcomes in early childhood settings.